Penerapan Asas Proporsionalitas Dalam Perjanjian Pembangunan Perumahan Antara Pengembang Dengan Pemilik Lahan - Yudhi wahab aprisandi; Dedi; Anantasiah Putri; Fathiya Geumala; Lindawati Saleh; Putri Sari Nilam Cayo (Consensus : Jurnal Ilmu Hukum, 2022)
The basic definition of proportionality is balance in everything, which means that everything is balanced materially, both in terms of profits and losses. Proportionality also includes balance according to the fair proportions that each party has. The author will discuss how the developer's obligations are regulated in the housing development cooperation agreement. A writer uses normative legal research, which uses library material or secondary data. Developers must keep the safety and security of landowners after they occupy the building that has been built. The rights of landowners must be protected by adhering to all agreements.